2002
DOI: 10.1359/jbmr.2002.17.11.2080
|View full text |Cite
|
Sign up to set email alerts
|

Evidence From the Aged Orchidectomized Male Rat Model That 17β-Estradiol Is a More Effective Bone-Sparing and Anabolic Agent Than 5α-Dihydrotestosterone

Abstract: This study was designed to evaluate the impact of estrogen versus androgen action on orchidectomy (ORX)-induced bone loss and associated changes in body composition. During an experimental period of 4 months, aged (12-month-old) ORX rats were treated with 17␤-estradiol (E 2 ; 0.75 g/day) or different doses of the nonaromatizable androgen 5␣-dihydrotestosterone (DHT; 45, 75, and 150 g/day, respectively), via subcutaneous (sc) silastic implants. Low doses of DHT and E 2 inhibited the ORX-induced rise of bone tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
0
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 31 publications
7
51
0
10
Order By: Relevance
“…In addition, this positive relationship was unrelated to the testosterone level as the association persisted after its adjustment ( Table 2). The role of estrogen receptor activation in the modulation of muscle mass remains unclear although some animal studies have revealed that estrogen receptor activation was involved in this process (32)(33)(34). Our results also revealed that total E 2 level, though positively related to muscle mass, was negatively related to muscle strength (Tables 2 and 4), in contrary to testosterone that was associated favorably with both muscle quantity and quality.…”
Section: Discussionsupporting
confidence: 45%
“…In addition, this positive relationship was unrelated to the testosterone level as the association persisted after its adjustment ( Table 2). The role of estrogen receptor activation in the modulation of muscle mass remains unclear although some animal studies have revealed that estrogen receptor activation was involved in this process (32)(33)(34). Our results also revealed that total E 2 level, though positively related to muscle mass, was negatively related to muscle strength (Tables 2 and 4), in contrary to testosterone that was associated favorably with both muscle quantity and quality.…”
Section: Discussionsupporting
confidence: 45%
“…In addition, there are indications that both ERa and ERb activation modulate muscle mass and/or function in mice (32,33). We also previously showed that E 2 , but not dihydrotestosterone, increased lean mass in orchidectomized, aged male rats (34). Finally, it is well established that estrogen treatment results in an anabolic effect on muscle mass in cattle (35).…”
Section: Discussionmentioning
confidence: 79%
“…Clinical trials investigating the effects of aromatase inhibition in older men showed no effect of the intervention on body composition or muscle strength (29,30) and, thus, did not support an important role of serum E 2 levels for lean mass in men. Nevertheless, animal studies have indicated that not only AR activation but also ER activation modulates lean mass (31)(32)(33)(34). It was recently demonstrated that ERa activation is required for normal muscle mass in male mice (31).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen has, in some previous studies, been shown to exert anabolic effects on muscle mass (47,48), suggesting that the effect on lean mass and muscle in COMT LL might also be a direct consequence of the elevated levels of estradiol.…”
mentioning
confidence: 95%